Nextgen engineers: empowering communities empower together for kids' safe, inclusive and innovative future 2.0 - UiTM, Fakulti Kejuruteraan Awam (Faculty of Civil Engineering, 2025)
Road safety awareness program was organised by the Faculty of Civil Engineering, UiTM Shah Alam to 50 pupils from five (5) different primary schools in the Seremban district on 21 June 2025. This program was the fifth edition of the Nextgen Engineers program and held at the UiTM Rembau Campus in collaboration with PERKESO (Social Security Organisation) and the Rembau District Education Office (PPD). The five participating schools were SK Pilin, SK Pedas, SK Salak Nama, SK Kampung Batu, and SK Bongek. The program was conducted under the Service Learning Malaysia - University for Society (SULAM) initiative through course ECC589 and advised by Associate Professor Ir. Dr.- Ing. Masria Mustafa. A total of 31 university student facilitators were involved, including 16 final-year students from the Faculty of Civil Engineering of UiTM Shah Alam and 15 students from UiTM Rembau Campus.